SMART settlement models based on international and hungarian initiatives - possible development paths for peripheral areas - Káposzta, József; Némediné Kollár, Kitti (Studia Mundi – Economica, 2017)
In terms of the Earth as a whole, the proportion of urban inhabitants exceeds half of the current population of the Earth, which proportion is likely to rise (based on preliminary estimates) in the future. In addition to the concept of SMART Cities, in May 2017, a pilot project called SMART Village was launched in the countryside. In both cases, the first step for the participants of the project was to define the exact definition, as well as good practices and models that can be used on the field. In this paper, we aim to review the conceptual delimitation of the SMART criteria and the available online database and how it can be adapted in Hungary. A number of SMART cities have launched territorial initiatives that can provide a good basis for implementing effective Integrated Urban Development Strategies for the future. In contrast, for SMART villages, the primary goal at the beginning in the current programming period is to create the SMART-Village reference points for which the financial resources will provided by the European Union. In this paper, we aim to find, interpret and define the SMART village, and to showcase Hungarian SMART initiatives through document analysis using "good practices" in Hungary (Alsómocsolád).